The outcast girls - Clare, Alys (Clare, Alys. World's End Bureau mystery, 2020)
"London, 1881. Lily Raynor, owner of the World's End Investigation Bureau, is growing increasingly worried. Work is drying up, finances are tight and she cannot find enough for her sole employee, Felix Wilbraham, to do. So when schoolteacher Georgiana Long arrives, with a worrying tale of runaway pupils, it seems like the answer to her prayers. The case is an interesting one, and what could be less perilous than a trip to a girls' boarding school, out in the Fens? Disguised as the new Assistant Matron, Lily joins the Shardlowes School staff, while Felix - suppressing his worries about his cool, calm employer - remains behind. But there are undercurrents at Shardlowes, and the shadowy, powerful men who fund the school's less fortunate pupils loom larger as Felix's own investigations unfold. Felix can't shake off his fear that Lily is in danger - and soon, his premonitions come frighteningly true . . ."--Provided by publisher.